"Broken windows": Relationship between neighborhood conditions and behavioral health among low-income African American adolescents. (March 2018) - Voisin, Dexter R; Kim, Dong Ha
This study explored the association between neighborhood conditions and behavioral health among African American youth. Cross-sectional data were collected from 683 African American youth from low-income communities. Measures for demographics, neighborhood conditions (i.e. broken windows index), mental health, delinquency, substance use, and sexual risk behaviors were assessed. Major findings indicated that participants who reported poorer neighborhood conditions compared to those who lived in better living conditions were more likely to report higher rates of mental health problems, delinquency, substance use, and unsafe sexual behaviors. Environmental factors need to be considered when addressing the behavioral health of low-income African American youth.